Neuronal Repressor REST Controls Ewing Sarcoma Growth and Metastasis by Affecting Vascular Pericyte Coverage and Vessel Perfusion - Zhou, Zhichao (Cancers (Basel), 2020)
Survival rates for Ewing sarcoma (ES) patients with metastatic disease have not improved in over 20 years. Tumor growth and metastasis are dependent on tumor vasculature expansion; therefore, identifying the regulators that control this process in ES may provide new therapeutic opportunities. ES expresses high levels of repressor element 1 silencing transcription factor (REST), which is regulated by the EWS-FLI-1 fusion gene. However, the role of REST in ES growth and the regulation of the tumor vasculature have not been elucidated. To study this role, we established REST-knockout human TC71 ES cell lines through CRISPR/Cas9 recombination. While knockout of REST did not alter tumor cell proliferation in vitro, REST knockout reduced tumor growth and metastasis to the lung in vivo and altered tumor vascular morphology and function. Tumor vessels in the REST-knockout tumors had a punctate appearance with significantly decreased tumor vascular pericytes, decreased perfusion, and increased permeability. REST-knockout tumors also showed increased apoptosis and hypoxia. These results indicate that REST plays a critical role in ES vascular function, which in turn impacts the ability of ES tumors to grow and metastasize. These findings therefore provide a basis for the targeting of REST as a novel therapeutic approach in ES.